Plant species effects on soil organic matter turnover and nutrient release in forests and grasslands - Scott, Neal Arthur, author; Binkley, Dan, advisor; Burke, Indy, committee member; Lauenroth, Bill, committee member; Ryan, Michael, committee member (Colorado State University. Libraries, 1996)
Although feedbacks between plant species and ecosystem dynamics have been demonstrated in a variety of terrestrial ecosystems, little research has examined the mechanistic relationship between plant species characteristics, the formation and turnover of soil carbon and nitrogen pools, and ecosystem processes such as net N mineralization. My objective was to examine two possible effects of species on soil C and N dynamics; changes in organic matter quality and changes in soil aggregation. For several forest ecosystems, litter lignin:N ratio correlated negatively (non-linear) with net N mineralization, but the relationship did not apply to grass species. Climatic factors (temperature, precipitation) explained little of the variation in net N mineralization. The relationship between litter lignin:N ratio and net N mineralization from mineral soil and the forest floor was similar, suggesting that plant litter quality affects both forest floor and mineral soil organic matter quality. For tree species monocultures in Wisconsin, net N mineralization during 387 day laboratory incubations indicated that species alter the quality of readily decomposable pools of soil N, and have little effect on more recalcitrant soil N. Changes in the quality of soil N correlated positively with in situ net N mineralization. Grass species did not influence N mineralization. Neither grass nor tree species influenced soil C dynamics, but differences in soil characteristics between sites influenced soil C dynamics. Soil microbes appear to act as a “decay filter”, converting heterogeneous plant material into relatively homogeneous soil humus. Changes in soil aggregate size distribution should alter whole-soil C and N quality because different size aggregates contain organic matter of different quality. Although tree species slightly altered aggregate size distribution, aggregate size distribution related poorly to whole-soil C and net N mineralization. Tree species had no effect on the physical protection of organic matter in soil aggregates or on organic matter quality of different size aggregates. Species characteristics had little effect on soil C mineralization, but species-related changes in the quality of readily decomposable soil N pools (not the pool size) influenced net N mineralization. This suggests that the feedbacks between plant species and soil N cycling occur rapidly, ensuring an adequate nutrient supply when plant community structure changes.
Keywords: Humus; Forest soils; Forest litter -- Biodegradation